Frequent somatic transfer of mitochondrial DNA into the nuclear genome of human cancer cells - Ju, Young Seok; Tubio, Jose M.C.; Mifsud, William; Fu, Beiyuan; Davies, Helen R.; Ramakrishna, Manasa; Li, Yilong; Yates, Lucy; Gundem, Gunes; Tarpey, Patrick S.; Behjati, Sam; Papaemmanuil, Elli; et al.

(untitled) (Genome Research, 2015)
Mitochondrial genomes are separated from the nuclear genome for most of the cell cycle by the nuclear double membrane, intervening cytoplasm, and the mitochondrial double membrane. Despite these physical barriers, we show that somatically acquired mitochondrial-nuclear genome fusion sequences are present in cancer cells. Most occur in conjunction with intranuclear genomic rearrangements, and the features of the fusion fragments indicate that nonhomologous end joining and/or replication-dependent DNA double-strand break repair are the dominant mechanisms involved. Remarkably, mitochondrial-nuclear genome fusions occur at a similar rate per base pair of DNA as interchromosomal nuclear rearrangements, indicating the presence of a high frequency of contact between mitochondrial and nuclear DNA in some somatic cells. Transmission of mitochondrial DNA to the nuclear genome occurs in neoplastically transformed cells, but we do not exclude the possibility that some mitochondrial-nuclear DNA fusions observed in cancer occurred years earlier in normal somatic cells.